HIV-1 subtypes and circulating recombinant forms (CRFs) from HIV-infected patients residing in two regions of central and southern Italy - Monno, Laura; Brindicci, Gaetano; Caputo, Sergio Lo; Punzi, Grazia; Scarabaggio, Teresa; Riva, Chiara; Bari, Cesare Di; Pierotti, Piera; Saracino, Annalisa; Lagioia, Antonella; Mazzotta, Francesco; Balotta, Claudia; et al. (Journal of medical virology, 2005)
A total of 347 pol gene sequences from 88 Tuscan and 259 Apulian subjects (including 52 non‐Italians and 9 children) were analyzed phylogenetically. Forty‐four (12.6%) non‐B subtypes were found, including 3.4% C, 1.4% F1, 0.8% G, and 0.3% each for J and A pure subtypes, and 3.7% CRF02_AG, 1.4% CRF01_AE, 0.6% BF, and 0.3% CRF06‐cpx recombinant forms. An additional sample close‐matched the pol gene of an unique recombinant form (URF AGK 99GR303). The non‐B subtypes were from 40 adults and 4 children; 12 of these 44 patients were epidemiologically linked. Thirty‐three of the 44 non‐B viruses pertained to non‐Italian immigrants and 11 to Italians, signifying that 63.4% immigrants and 3.7% Italians harbored non‐B subtypes. The overall frequency of non‐B subtypes was higher in Tuscany than in Apulia (18.1% vs. 10.8%). Moreover, 6.1% and 3.0% non‐B subtypes were found among Italians from Florence and Apulia, respectively, while 52.1% and 72.4% of immigrants living in Tuscany and Apulia harbored non‐B subtypes. Women infected by means of sexual contact prevailed among non‐Italian adults; the majority of Italians were males and admitted high‐risk sexual behavior. Four Italians had a history of extensive travel in countries of high endemicity. Social and epidemiological changes are responsible for an increasing circulation of non‐B subtypes in Italy. Although non‐B subtypes principally infect non‐Italian patients, in Italy they can no longer be considered exclusively restricted to subjects from endemic areas. J. Med. Virol. 75:483–490, 2005. © 2005 Wiley‐Liss, Inc.